Drivers of Youth Outsiderness in European Labour Markets. A Comment on Marques and Salavisa (Socio-Economic Review, 2017) - Svenja Flechtner; Torsten Heinrich (Journal of Comments and Replications in Economics (JCRE), 2025)
Marques and Salavisa (2017) use fuzzy set qualitative comparative analysis (fsQCA) to analyze agebased labour market dualization in Southern European, Anglo-Saxon and a few Nordic countries. They argue that segmentation at the expense of young outsiders is driven by several factors in non-linear ways: deindustrialization, labour market coordination, employment protection, and liberalization can lead to youth outsiderness. We are able to replicate their analysis in technical terms, but argue that the analysis and the interpretation of its results are subject to technical misunderstandings. When correcting for these, we must call into question the study's results. To underpin our argument, we provide a hands-on discussion of how two measures of fit in fsQCA - the consistency and PRI scores of the sufficiency solution terms - are calculated. A good understanding of these allows the researcher to understand which cases and configurations drive the results, and thus facilitates technically correct decisions during the analysis and a better understanding of the results. We conjecture that the original paper cannot present conclusive evidence on the hypotheses it sought to test for a lack of sufficient variation in the empirical data sample.
https://doi.org/10.15456/j1.2025143.1723742063
Keywords: J50; J40; 330; Labour market dualization; Youth outsiderness; FsQCA; Replication; Sufficiency score